Multi-dimensional visual information processing under complex light environments using time-evolved polarization-sensitive synaptic electronics - Yaqian Yang; Wenhao Ran; Ying Li; Yancheng Chen; Di Chen; Guozhen Shen (Nature Communications)
Abstract Biological vision system-inspired optoelectronic synapses integrate sensing, memory, and processing for external information perception. However, most efforts focus on spatial expansion while overlooking critical dimensions like polarization and temporal evolution, which are critical for information extraction in complex environments. Inspired by the polarization-sensitive properties of kingfisher vision, we develop a polarization-sensitive optoelectronic synapse array device based on PEA2SnI4 microwires array. Their anisotropic properties ensure polarization recognition, achieving a dichroic ratio of 1.38. And the asymmetric electrode designs create differentiated contact barriers, facilitating efficient charge storage and erasure under low power consumption. By employing four polarization-state-dependent convolutional kernels, the device demonstrates edge extraction capabilities even under 50% salt pepper noise. Furthermore, it enables high-precision in-sensor reservoir computing, with 100% accuracy in extracting fish trajectories under complex light environments. This work demonstrates motion perception in complex environments and provides a foundation for developing multi-dimensional, time-resolved visual systems for intelligent sensing and recognition.